Low-dose peripheral blood stem cell graft after high-dose chemotherapy - an evaluation of hematopoietic reconstitution - Sauer, Sandra; Pavel, Petra; Schmitt, Anita; Cremer, Martin; Kriegsmann, Mark; Bruckner, Thomas; Jordan, Karin; Wuchter, Patrick; Müller-Tidow, Carsten; Kriegsmann, Katharina (BMC cancer, 2020)
High-dose (HD) chemotherapy followed by autologous blood stem-cell transplantation (ASCT) is the standard treatment for multiple myeloma (MM) patients. However, the collection of sufficient peripheral blood stem cell (PBSC) grafts can be challenging, and the question arises whether reinfusion of low-dose grafts will lead to a hematopoietic recovery.